Formula of Recycled Concrete Aggregate Compressive Strength in Mix Design - Suharwanto Suharwanto; Munaf D R (International Conference on Engineering and Technology Development (ICETD), 2017)
The development of material for concrete has advanced rapidly and many alternative aggregate as base material for concrete has found to reduce the natural aggregate that has been took from stone mining, such as recycled aggregate, ALWA (Artificial Lightweight Aggregates), glass as aggregate, and other material that can replace aggregate in the concrete. Those aggregate alternative aim to reduce the using of natural aggregate. This paper only explain recycle aggregate. The name of concrete that is made from recycle aggregate (RA) is called Recycle Concrete Aggregate (RCA). The experimental of RCA in the mix design of concrete that made from recycle concrete has been done to find out the formula of compressive strength design of concrete mix design. The sample has been made more than 100 cylinder specimens that three specimens for each strength. The variation of recycle aggregate is made from variation of normal concrete strength that is made for 25, 30, 40, 50, 65, 70 and 80 MPa and the variation of percentage of recycle aggregate contain is 50 and 100%. Base on the experiment result the strength of RCA is decrease the compressive strength from the natural concrete. The decreasing of normal compressive strength is about 20 to 25% under the original compressive strength of concrete and about 26 to 35% for high strength concrete. Keywords—component; Concrete Mix Design, Natural Aggregate (NA), Recycle Aggregate (RA), Recycle Concrete Aggregate (RCA), Compressive Strength, Normal Compressive strength of concrete, High Compressive strength of concrete.